Legal Protection for Online Game Users Against Cheating in Championships - Aji, Wisnu Kuncoro; Rusdiana, Emmilia (NOVUM : JURNAL HUKUM, 2025)
The development of information technology is experiencing rapid development and has penetrated into all sectors both in terms of economy, business, industry, even in the entertainment world it also has its own technology. One technology that has penetrated the world of entertainment is consoles and video games. Someone plays games with the aim of just entertainment, notinfrequently they play games with the aim of achieving popularity in the game and to achieve the highest score. Seeing the number of enthusiasts in a game, there are time when gamers appear who want an instant achievement, by making system changes or entering fake commands called cheats. The addition of this cheat system in a game makes it easier for players to achieve their goals, but making other players cheat by playing fair causes the game to be unfair. The purpose of this study is to find out the legal regulations for using cheats in the games against the laws in force in the Republic id Indonesia, including the Criminal Code and the ITE Law. The legal sources in this research are literature, legislation, journals, and relates articles, the data collection method in this study used literature study and literature study.